THE RECENT TRANSITION FROM GLACIAL TO PERIGLACIAL ENVIRONMENT IN A HIGH ALTITUDE ALPINE BASIN (SABBIONE BASIN, NORTH-WESTERN ITALIAN ALPS). PRELIMINARY OUTCOMES FROM A MULTIDISCIPLINARY APPROACH - COLOMBO, NICOLA; BUFFA, Giorgio; FRATIANNI, SIMONA; Giaccone, Elisa; Paro, Luca (2016)
High Alps are characterised by glacial and periglacial environments, which change sensitively in response to climatic changes. The global warming that has been witnessed over the last few decades has caused remarkable effects on high altitude mountain zones. In order to assess the ongoing transition from glacial to periglacial environments, due to climate change, and its effects on cryosphere, geosphere and biosphere, a multidisciplinary approach has been applied in the Sabbione Basin (Italy). In this study, attention has mainly been paid to two selected areas (pilot sites) representative of glacial-periglacial interactions in the investigated basin. Climatological and geomorphological studies have been conducted, together with analyses on the potential permafrost distribution. Furthermore, floristic surveys have been carried out to characterise the vegetation within the periglacial sites and Artemisia genipi has been selected as the monitoring species because of its abundance and its late flowering season. The climatic analyses have indicated that, over the last decades, air temperatures have increased and snow cover duration and thickness have decreased, thus causing a substantial regression of the glaciers. Periglacial processes and new permafrost-related landforms have been developing in recently deglaciated areas. The distribution, reproductive state and phenology of the monitoring species show a clear relationship with the permafrost-related landforms (i.e. rock glaciers). Moreover, the phenological delay observed in some of the Artemisia genipi individuals shows that micro-morphology and cold water sources have a considerable influence on their development. Finally, it has been found that lower altitude plant species have been colonising the basin, indicating an upward shift due to global warming conditions.